Morbidity Occurs to a Fifth of Referred Post Partum Hemorrhage Cases - Fitri Rahardja (Indonesian Socety of Obstetrics and Gynecology, 2013)
Objective: To assess maternal morbidity (five scoring system) and mortality of referred post partum hemorrhage (PPH) in Dr. CiptoMangunkusumo Hospital period 2008-2010 and to identify its related factors. Method: Retrospective study with cross sectional design for referred obstetric cases in RSCM period 2008-2010. Analysis of relation was conducted to these data using Chi-square or Fisher test with SPSS 17.0. Result: There were 10,752 referred obstetrics cases in RSCM from 2008-2010, the three most common cases were severe preeclampsia, premature rupture of membrane, and preterm labour. The rate of referred cases of PPH in RSCM from 2008-2010 was 2%. There were 44 cases (20.5%) suffering morbidity (five scoring system) and 3 cases ending in mortality (1.4%) from all PPH referral cases. Mortality to morbidity rate for referred PPH cases in RSCM was 6.81% (3/44) with case/fatality ratio 14.7: 1. Variables that related to morbidity were age and referral factors (midwife). There were no relation between parity, education background, pay of services, occupation, type and etiology of PPH with morbidity due to PPH. Mortality assesment for 3 PPH referred cases would be descriptive. Conclusion: The proportion of referred PPH cases in RSCM 2008-2010 was 2%, of which 20.5% classified as morbid and 1.4% was classified as mortal cases. Variables related significantly to morbidity were age and referral factors. [Indones J Obstet Gynecol 2013; 37-1: 3-7] Keywords: five scoring system, maternal morbidity, maternal mortality, referred cases of PPH